Efficiency and thermography in cycling during a graded exercise test - Duc, S.; Arfaoui, A.; Polidori, G.; Bertucci, W. (Journal of Exercise, Sport & Orthopedics, 2015)
During cycling exercise, at least 75% of energy expended is wasted as heat or used to maintain homeostasis regard to the consistent value of Gross Efficiency (GE), Net Efficiency (NE) and Delta Efficiency (DE) reported in the literature (18 - 26%). Therefore, it would be assumed that potential link exists between cycling efficiency and thermoregulation process. Skin temperature of two lower limb muscle's group (quadriceps and calves) detected by infrared camera and cycling efficiency parameters determined by gas exchanges analysis were measured during a graded exercise test until exhaustion in seven trained young cyclists.